Algoritma K-Means untuk Pengelompokkan Dokumen Akta Kelahiran pada Tiap Kecamatan di Kabupaten Simalungun - Napitupulu, Flora Sabarina; Damanik, Irfan Sudahri; Saragih, Ilham Syahputra; Wanto, Anjar (Forum Kerjasama Pendidikan Tinggi, 2020)
A birth certificate is a document that must be owned by a citizen. This document contains information about the birth of a person and is an official record of proof of state recognition of the person's existence. The purpose of this study is to group birth certificate documents in each district in Simalungun Regency. The research data was obtained from the Population and Civil Registry Office of Simalungun Regency. The grouping algorithm used is the K-means algorithm which is one of the Data Mining algorithms that is good for the case of grouping. By using this algorithm the data that has been obtained can be grouped into several clusters, where the application of the K-Means Clustering process uses the RapidMiner tool. Data is divided into 3 groups: high (C1), medium (C2) and low (C3). The results obtained from this study are in December entered into a high level cluster (C1), in August, September and October entered into a medium cluster (C2), and in January, February, March, April, May, June, July and November entered into the low cluster (C3).